2001
DOI: 10.1080/13607860120080350
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric evaluation of a brief geriatric depression screen

Abstract: This article is a psychometric evaluation of the experimental Geriatric and Extended Careline Depression Screen (GEDS) for geriatric nursing care residents. The GEDS is a five-item depression screen based on an abbreviated version of the Center for Epidemiological Studies Depression Scale (CES-D). A total sample of 91 male residents over the age of 60 were recruited from a Veterans Administration Nursing Home Care Unit. The Geriatric Depression Scale-Short Form (GDS-SF) was used as a gold standard test to exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
0
9
0
2
Order By: Relevance
“…The GDS Short Form (GDS-SF) consists of 15 items extracted from the GDS. Lelito et al (2001) found the short form to be as effective as the original form in identifying depression (14). Studies show a high correlation between the long and short form ( r = 0.91, p <.01) (12).…”
Section: Objectivesmentioning
confidence: 99%
“…The GDS Short Form (GDS-SF) consists of 15 items extracted from the GDS. Lelito et al (2001) found the short form to be as effective as the original form in identifying depression (14). Studies show a high correlation between the long and short form ( r = 0.91, p <.01) (12).…”
Section: Objectivesmentioning
confidence: 99%
“…Depressive Symptoms. Depressive symptoms were measured using the Geriatric Depression Scale (GDS; 30-item scale; Lelito, Palumbo, & Hanley, 2001). The tool was initially validated in adults ³55 yr old recruited from housing projects or senior centers or hospitalized for depression in one U.S city.…”
Section: Methodsmentioning
confidence: 99%
“…Given the popularity of the GDS as a screening instrument for depression (e.g., Gerrard et al, 1998;Lelito, Palumbo, & Hanley, 2001), it is important to conduct an investigation into this issue. We frame this question as whether inclusion of the six WAV items on the GDS, which make up 20% of this 30-item scale, would influence the diagnostic outcome of the GDS.…”
Section: Introductionmentioning
confidence: 99%